Birth Prevalence of Anorectal Malformations for the Western Cape Province, South Africa, 2005 to 2012 - Theron, Andre; Numanoglu, Alp (European Journal of Pediatric Surgery, 2017)
Introduction Anorectal malformations (ARMs) are a major birth anomaly worldwide. South Africa has ethnically and geologically diverse populations. A recent publication indicated an increased birth prevalence of ARMs in the Witwatersrand referral area between 2005 and 2010. The purpose of this study was to determine the birth prevalence of ARM and its various subtypes in the Western Cape referral district over an 8-year period.Methods For an 8-year period from January 1, 2005, to December 31, 2012; retrospective data were collected from the Pediatric Surgical Departments of Red Cross War Memorial Children's Hospital, Tygerberg Children's Hospital, as well as the private sector health registries. The number of live births per year for a specific municipal district was obtained from the National Department of Health. The chi-square for trend test was used to determine statistical significance.Results The birth prevalence for ARM in the Western Cape Province (WCP) in 2012 was shown to be 1:5,572 live births (1.79/10,000 live births). The West Coast municipality district had the highest average birth prevalence rate of 1:3,063 (3.26/10,000) live births for years studied. There was a male predominance (1.6:1), the most common ARM was the vestibular fistula (19.2%) and in 26% of the patients, there was an initial delay in the diagnosis.Conclusion This study has provided some recent data for ARMs for the WCP. There was no statistical significant change in the prevalence of ARMs over the 8-year period for the WCP as well as in any of the individual six municipal health districts (χ2 for trend, p = 0.52). The number of delayed diagnosis of ARM is of concern.
Keywords: anorectal malformation; prevalence; delayed diagnosis; South Africa; Western Cape Province